2020
DOI: 10.1002/jor.24898
|View full text |Cite
|
Sign up to set email alerts
|

SM04755, a small‐molecule inhibitor of the Wnt pathway, as a potential topical treatment for tendinopathy

Abstract: The Wnt pathway is upregulated in tendinopathy, affecting inflammation and tenocyte differentiation. Given its potential role in tendinopathy, this signaling pathway may be a relevant target for treatment. The current study examined the therapeutic potential of SM04755, a topical, small-molecule Wnt pathway inhibitor, for the treatment of tendinopathy using in vitro assays and animal models. In vitro, SM04755 decreased Wnt pathway activity, induced tenocyte differentiation, and inhibited catabolic enzymes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 57 publications
4
29
1
Order By: Relevance
“…Alternative splicing of Tau exon 10 is regulated by CLK2 and other CLKs, leading to changes in the 3R/4R isoform ratio and neurodegeneration in sporadic AD [ 224 , 225 ]. Dual inhibitions of CLK2 and DYRK1A by Lorecivivint (SM04690) and by its analogue SM04755 are potential disease-modifying approaches for knee osteoarthritis [ 193 , 194 ] and for tendinopathy, respectively [ 195 ]. CLK2 inhibition compromises MYC-driven breast tumors, triple-negative breast cancer, and glioblastoma.…”
Section: Clks and Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Alternative splicing of Tau exon 10 is regulated by CLK2 and other CLKs, leading to changes in the 3R/4R isoform ratio and neurodegeneration in sporadic AD [ 224 , 225 ]. Dual inhibitions of CLK2 and DYRK1A by Lorecivivint (SM04690) and by its analogue SM04755 are potential disease-modifying approaches for knee osteoarthritis [ 193 , 194 ] and for tendinopathy, respectively [ 195 ]. CLK2 inhibition compromises MYC-driven breast tumors, triple-negative breast cancer, and glioblastoma.…”
Section: Clks and Human Diseasementioning
confidence: 99%
“…Tendinopathy [195] DYRK1A Human immunodeficiency virus type 1 (HIV-1) [196][197][198] DYRK1A DYRK1B Human cytomegalovirus (HCMV) [199] DYRK1B…”
Section: Dyrk1amentioning
confidence: 99%
“…It has entered phase 1 trials as an oral pan-CLK inhibitor (CLK2 IC 50 = 2 nM) for the treatment of advanced solid tumors. , Notably, CLK3 (IC 50 = 22 nM) was also inhibited by compound 4 . Recently, Biosplice reported that indazole-3-carboxamide derivative 5 (SM04755, Table , Figure A) guided by a structure–activity relationship (SAR) exhibited picomolar activity in enzymatic assays (CLK2 IC 50 = 0.822 nM) and lower nanomolar activity in cellular assays (cell CLK2 EC 50 = 268.1 nM). Docking studies suggested that 5 formed hydrogen bonds with Glu244, Leu246, and Lys193 in the ATP-binding site of CLK2 . However, the phase 1 trial for the treatment of plaque psoriasis was terminated based on various commercial factors…”
Section: Clk2 Inhibitors In Clinical Developmentmentioning
confidence: 99%
“…Conversely, dysregulated alternative splicing can be a root cause of developmental disorders, tissue degeneration, and cancer . Owing to their pivotal role, pharmacological inhibitors of CLK2 have been regarded as potential drugs for various diseases including inflammation (e.g., osteoarthritis, tendinopathy), cancers (e.g., triple-negative breast cancer), neurodegenerative diseases (e.g., Alzheimer’s disease), and metabolic diseases (e.g., diabetes). ,,, …”
Section: Future Perspectivesmentioning
confidence: 99%
“…Much effort has been devoted to discovering inhibitors of the Wnt/β-catenin signaling pathway . Among them, porcupine inhibitors (LGK-974, RXC004, CGX1321, and ETC-159), Fzd receptor-related monoclonal antibodies (OMP-18R5 and OMP-54F28), CREB-binding protein (CBP)/β-catenin inhibitors (PRI-724 and CWP232291), and CLK2 and DYRK1A inhibitors (SM04690, , SM04755, and SM08502) have been tested in the clinic. Most of these reported inhibitors, also including tankyrase inhibitors (XAV939), target the upstream effectors of Wnt/β-catenin signaling, whereas these agents are forecasted to be ineffective toward the diseases related with more downstream APC and Axin inactivation mutations or β-catenin activation mutations.…”
Section: Introductionmentioning
confidence: 99%